2010
DOI: 10.1063/1.3304919
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling microscopic analysis of Cu(In,Ga)Se2 epitaxial layers

Abstract: Scanning tunneling microscopy (STM) measurements have been made on single-crystal epitaxial layers of CuInSe2 grown on GaAs substrates. Results were obtained for as-grown, air-exposed, and cleaned surfaces; in situ cleaved surfaces; surfaces sputtered and annealed in the STM system; and samples prepared by a light chemical etch. Conventional constant-current topographs, current-voltage curves, and current imaging tunneling spectroscopy (CITS) scans were obtained. Topographic images show that the surfaces appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…To illustrate the differences between AIS and CIS, we compare the present data to previously obtained STS data on CIS [29]. Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…To illustrate the differences between AIS and CIS, we compare the present data to previously obtained STS data on CIS [29]. Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Fig. 5b shows band edge fluctuation data for three sections of a line spectrum constructed from data in Mayer et al [29], denoted by circles, triangles, and squares.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[12] The nature of the defects giving rise to the band tails is currently unknown, although one may presume that individual point defects or defect clusters have a strong effect on the results. [10] Here we present further data on the effect of point defects in CIS on local electronic structure of the material at the atomic scale.…”
Section: Introductionmentioning
confidence: 98%
“…Excellent performance has been replicated at a number of laboratories with the highest performance near 20% efficiency. [1] A wide range of studies, primarily using photoluminescence, of CuInSe 2 have shown significant band tails to occur in these materials [2][3][4][5][6][7][8][9][10][11] In one study it was concluded that the performance of solar cells may depend directly upon the band tail width. [12] The nature of the defects giving rise to the band tails is currently unknown, although one may presume that individual point defects or defect clusters have a strong effect on the results.…”
Section: Introductionmentioning
confidence: 99%